Sports Radiology : Making a diagnosis or solving a problem - George, J. (Publisher Medimond Publishers, 2014)
A Musculoskeletal Radiologist who images Sports Injuries has a major role of detecting the cause of the patients current symptoms which is their current problem which affects their performance and quality of life